THE IMPORTANCE OF THE DEVELOPMENT OF SMALL ENTERPRISES AND THE SPECIFICS OF ORGANIZATION OF ITS ACCOUNTING TAXATION - O. S. D’yakonova; A. M. Puzankova (Вестник университета, 2019)
The arguments, justifying the need to create a unified legislative framework, governing the accounting system of small enterprises, have been presented. The modern interpretations of the concept “small enterprise” have been considered. The criteria for classifying an enterprise as small in accordance with the legislative acts of the Russian Federation have been summarized. The features of accounting by small enterprises, which suggest a choice between a general or simplified accounting system, have been highlighted. Specific taxation systems for small enterprises have been determined and compared.